UUM's Library Reminder System - Mansour, Mohammed Ben Sharrada (2009)
According to the 9th and 10th rules in the Sultanah Bahiyah Library, students are responsible for the returning or books borrowed on/before the due date; fines will be imposed on late return of materials borrowed. The delay of return will also affect the well balanced flow of the books. In order to solve the problem, a UUM's Library reminder system is proposed in this research to remind the students to return books on time. The proposed system will follow the General Methodology of Design Research introduced by Vaishnavi and Kuechler. Following this methodology, the awareness of problem and suggestion is made first, after the development of the system, evaluation is conducted and finally conclusion is made. This system is hoped to make the library's daily operation more efficient and help the students to avoid punishment of delay to return books.